Thirukkural Alagiduthal and Kural Venba Validation using Python - S, Thivaharan; C, Gayathri; M, Vijay Raj Kumar (Journal of Trends in Computer Science and Smart Technology, 2023)
Thirukkural, one of the prominent Tamil Literatures, written 2000 years ago, has great importance till date as it emphasizes everyday virtues of the individuals. As per Tamil Literature, it belongs to the class of ‘Kural Venba’ which is a subdivision of ‘Venba’ and is regarded as one of the poetic styles of Tamil Language. This research primarily aims on the validation of entered Thirukkural by checking the syntactical correctness of ‘Kural Venba’. It uses ‘Transliteration’ methodology to convert the user given thirukkural into an intermediate form. Then, it processes the intermediate form to segregate the words (seer and thalai) into different asai as per the Yaapilakkanam known as Alagiduthal, compares it with the pre-defined norms of ‘Kural venba’ and produces the result. At any point of time, if the user input doesn’t qualify a criterion, the program outputs a warning accordingly and gets terminated.
Keywords: Transliteration; Alagiduthal; Seer; Thalai; Kural Venba; Yaapilakkanam